Link-based And Subpath-based Hybrid Restoration Scheme In Optical Networks - Satria Utama; Istikmal Istikmal; Erna Sri Sugesti (eProceedings of Engineering, 2015)
Abstract—In optical network survivability, link-based and subpath-based restorations have been discussed in many papers as survivability methods for optical wavelength division multiplexing (WDM) network. One of the problem in both restoration methods occurs when network resources are unavailable. In such condition, the traffic is dropped and the source node is requested to retransmit the packages. This paper proposes LinkSPath, a hybrid scheme to increase the performance of network survivability by integrating both link- based and subpath-based restoration schemes. The scheme provides a redundancy for each other when one is not succeed due to unavailable resources. It also provides lightpath options and choose one with the shortest recovery time. The alternative lightpath with shortest recovery time is stated as the primary backup, while the other one as the secondary backup. The hybrid scheme is distributed and recovery times of both link- based and subpath-based are first calculated. Alternative lightpaths are determined using Dijkstra algorithm. The NSFNET modelwas utilized. The simulation showed that the LinkSPath scheme has average restoration time which complies with ANSI standard and would not jeopardize communication. It also showed that LinkSPath has improved the individual performance of forming methods, Link-Based and Subpath- Based, in the number of restorations with recovery time smaller than retransmission. Keywords—Optical networks; Survivability; Hybrid restoration; Link-based; Subpath-based; WDM networks